Provider satisfaction with office-based treatment of opioid dependence: a systematic review. - Becker, William C; Fiellin, David A (Substance abuse : official publication of the Association for Medical Education and Research in Substance Abuse, 2005)
New federal regulations allow for office-based treatment of opioid dependent patients with opioid agonist medication (e.g., buprenorphine). We sought to evaluate the literature on office-based physicians' acceptance of this practice.
Keywords: Ambulatory Care; Attitude of Health Personnel; Buprenorphine; Cooperative Behavior; Humans; Methadone; Narcotics; Opioid-Related Disorders; Patient Care Team; Physician-Patient Relations; Physicians, Family